Validating the primary care posttraumatic stress disorder screen for DSM-5 (PC-PTSD-5) in a substance misusing, trauma-exposed, socioeconomically vulnerable population. (April 2023) - Patton, Samantha C.; Hinojosa, Cecilia A.; Lathan, Emma C.; Welsh, Justine W.; Powers, Abigail
Highlights: Screening for posttraumatic stress disorder (PTSD) is not routinely conducted in substance use disorder (SUD) programs, despite clinical relevance. Screening for PTSD can be completed using a brief five item screening tool. A cut-score of 5 was found to be optimal in the current study population. Abstract: The co-occurrence of substance use disorder (SUD) and posttraumatic stress disorder (PTSD) is common, and is associated with greater severity of symptoms, poorer treatment prognosis, and increased risk of return to substance use following treatment. Screening for PTSD is not routinely implemented in substance use treatment programs, despite clinical relevance. Identifying screening tools that minimize patient burden and allow for comprehensive treatment in this patient population is critical. The current study examined the utility of the Primary Care PTSD Screen for DSM-5 (PC-PTSD-5) in identifying probable PTSD in a predominantly Black sample of 81 socioeconomically disadvantaged substance misusing hospital patients. The majority of the sample (75.3 %; n  = 61) were found to meet criteria for probable PTSD using a suggested clinical cut score of 33 on the PTSD Checklist for DSM-5 (PCL-5). Diagnostic utility analyses were completed and determined a cut-score of 5 for the PC-PTSD-5 to demonstrate the best performance (SE = 0.62, κ(1) = 0.22; SP =.80, κ(0) = 0.61; EEF = 0.67, κ(0.5) = 0.32) in this sample. Results provide preliminary support for the use of the PC-PTSD-5 as a brief screening tool for probable PTSD in substance misusing patient populations. Routine use of the PC-PTSD-5 during assessment may be beneficial when treatment planning with those undergoing treatment for SUD because comprehensive assessment and treatment will provide a better chance of long-term recovery.